1999
DOI: 10.1016/s0893-133x(99)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-2 Receptors and Human Sleep Effect of a Selective Antagonist on EEG Power Spectra

Abstract: To investigate the effect on the sleep EEG, a 1-mg oral dose of SR 46349B, a novel 5-HTThe pivotal role of serotonin (5-hydroxytryptamine, 5-HT) in sleep regulation has been the mainstay of the monoamine theory of sleep (Jouvet 1972). Although the views about the functions of this neurotransmitter have evolved, there is little doubt about its involvement in sleep mechanisms (McCormick 1992). Serotonergic neurons of the nucleus raphe dorsalis are most active during wakefulness and have been proposed to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 36 publications
3
64
0
1
Order By: Relevance
“…5-HT 1A agonists have been shown to suppress REM sleep (Driver et al 1995;Gillin et al 1994). Regarding SWS, drugs antagonising 5-HT 2A or 5-HT 2C demonstrate an enhancing effect on SWS (Landolt et al 1999;Sharpley et al 1994), whereas 5-HT 2C agonists appear to lower SWS (Katsuda et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT 1A agonists have been shown to suppress REM sleep (Driver et al 1995;Gillin et al 1994). Regarding SWS, drugs antagonising 5-HT 2A or 5-HT 2C demonstrate an enhancing effect on SWS (Landolt et al 1999;Sharpley et al 1994), whereas 5-HT 2C agonists appear to lower SWS (Katsuda et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Both the firing of serotonergic neurons in the raphe nuclei and serotonin release increase during waking, decrease in non-REM sleep and are absent during the REM stage (McGinty and Harper 1976). This regulation mechanism is very complex and involves the interplay of several serotonin receptor subtypes, with 5-HT 1A agonism suppressing REM sleep (Driver et al 1995), 5-HT 2A , 5-HT 2C antagonism enhancing slow-wave sleep (SWS) (Landolt et al 1999) and 5-HT 2C agonism decreasing SWS (Katsuda et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sleep disturbances (Landolt et al, 1999) and sexual dysfunction (Sargent et al, 1998) are preferentially associated with the 5-HT2A receptor and it has been reported that SSRI-induced gastrointestinal side effects are mediated by the 5-HT3 receptor (Bergeron and Blier, 1994). To our knowledge, there have been no previous studies investigating the relationship between polymorphisms of the 5-HT3A and 3B genes and the gastrointestinal side effects induced by SSRI.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether this polymorphism also modulates availability of other 5-HT receptor subtypes. Notwithstanding, it may contribute to inter-individual differences in the efficacy of currently emerging hypnotics that improve sleep via a serotonergic mechanism of action [140,141].…”
Section: Serotonin Transporter Gene (Slc6a4)mentioning
confidence: 99%